2017
DOI: 10.1017/s0021859617000223
|View full text |Cite
|
Sign up to set email alerts
|

Tillering dynamics of Mulato grass subjected to strategies of rotational grazing management

Abstract: SUMMARYPlants’ ability to rebuild their tiller population is affected by weather changes and management strategies. The hypothesis of the present study was that frequency and severity of defoliation alter Mulato grass (Brachiaria ruziziensis × Brachiaria brizantha cv. Marandu) sward development, and the proportion of aerial and basal tillers, interfering with sward stability. The objective was to evaluate aerial, basal and total tiller population density and changes in tillering dynamics. Treatments correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…Therefore, it is possible that the autumnal renewal of tillers is associated with a tillering strategy that Matthew et al (2000) referred to as a "reproductive mechanism", according to which the highest renewal of tillers in pastures is associated to the death of reproductive tillers and to the appearance of new tillers from the bud bank of the plants. The highest-tiller appearance rates observed in the lower-management heights corroborate the results obtained by Giacomini et al (2009) and Silva et al (2017), who showed that pastures of 'Marandu' and 'Mulato' palisadegrass, managed with 95% of light interception, showed the highest-tiller appearance rates, in comparison to those managed with about 100% light interception. The higher-grazing intensity at the 12 cm height pastures certainly allowed a higher-light intensity to reach the base of the plants, a condition that allows of the differentiation of the buds and the appearance of new tillers (Matthew et al, 2000).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it is possible that the autumnal renewal of tillers is associated with a tillering strategy that Matthew et al (2000) referred to as a "reproductive mechanism", according to which the highest renewal of tillers in pastures is associated to the death of reproductive tillers and to the appearance of new tillers from the bud bank of the plants. The highest-tiller appearance rates observed in the lower-management heights corroborate the results obtained by Giacomini et al (2009) and Silva et al (2017), who showed that pastures of 'Marandu' and 'Mulato' palisadegrass, managed with 95% of light interception, showed the highest-tiller appearance rates, in comparison to those managed with about 100% light interception. The higher-grazing intensity at the 12 cm height pastures certainly allowed a higher-light intensity to reach the base of the plants, a condition that allows of the differentiation of the buds and the appearance of new tillers (Matthew et al, 2000).…”
Section: Resultssupporting
confidence: 89%
“…agropec. bras., Brasília, v.54, e00405, 2019 DOI: 10.1590/S1678-3921.pab2019.v54.00405 in cultivated C 4 plants, such as those belonging to the Brachiaria genus, a similar pattern of response was observed, with a high-population recomposition occurring during the late spring (Silva et al, 2017). However, the appearance of tillers in the early autumn, which is relatively uncommon in warm season perennial species (Silva et al, 2015), is associated with low rates of tiller appearance in summer.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The stability of the population of aerial tillers showed a greater variation in relation to the basal ones. This occurred certainly because aerial tillers have a short life, since they are located in the grazable stratum, which facilitates their removal during defoliation (Santos et al, 2014), as well as they are highly dependent on basal tillers for nutrition, water supply, and support (Silva et al, 2017). Within the evaluated period, no strategy contributed to the degradation of the forage plant (Sousa et al, 2019).…”
Section: Gen 16 Gen 17 Gen 18 Gen 19mentioning
confidence: 99%
“…It is also possible that the basal tillers of the treatments with 20 cm height after defoliation, due to less forage removal, had reached an advanced stage of development, which may have favored the activation of axillary buds and, consequently, favored the aerial tillering that can be an important competition strategy for forage plants. Despite being generally short-lived and highly dependent on basal tillers for nutrition, water supply, and support (Silva et al, 2017), aerial tillers have a high share of leaves and have softer stems, allowing of a better nutritional value, in addition to being located in the grazable stratum, which facilitates their apprehension by animals for forage (Santos et al, 2014). In fact, aerial tillers of 'Survenola' digit Figure 3.…”
Section: Gen 16 Gen 17 Gen 18 Gen 19mentioning
confidence: 99%